“Ex-gordinhas: Uma Alma Indecisa. - Oliveira, Isabela Karolina Gomes Ferreira (2018)
This research has the objective of reflecting on the problematic related to the cult of the body that hangs, impositively, on the feminine universe. For this, based on the theoretical-methodological advice of the French-Speech Discourse Analysis, in terms of empirical observation data, the study draws on Discursive Sequences (DSs) from ex-chubby testimonials published by Women’s Health Brazil magazine. As specific objectives, we seek to: 1) Investigate the alleged relationship of "logical" consequence created by the magazine between the possession of a "fat" body and the suffering of certain "disadvantages", 2) To analyze the supposed "logical" consequence relation created by it between the “conquest” of a lean body and the attainment of certain “benefits”? and 3) To verify the position of the “ex-chubby” in relation to its old/current body and, more polemically: it is sought to understand the extent to which the "ex-chubby" in fact assume the discourse they say spokespersons. The chapters of analysis are intended to contemplate these questions. Therefore, in the first one, it is sought to show how the fat body is discursive by the deponents and one can perceive that the affirmations of them corroborate a reading of derogatory, demeritory and pejorative bias. On the other hand, in the second, it is verified that the lean body discursed by the “ex-chubby” receives another sense, since it is characterized as positive and beneficial. Finally, in the last chapter of the analysis, the objective is to understand to what extent the discourses about the lean body and the fat body are affectively assumed by them, since there are marks of a ritual that fails in terms of attending discursive predictability. In this chapter, in particular, it is evident how the female body is subjected to an imperative (or propagating) industry of thinness that directly affects women and their corporeality.